2015
DOI: 10.17795/rijm28277
|View full text |Cite
|
Sign up to set email alerts
|

Levamisole, Aminorex, and Pulmonary Arterial Hypertension: A Review

Abstract: Context: An epidemic of aminorex-associated pulmonary arterial hypertension (PAH), resulting in multiple fatalities, occurred in the 1970s ending only after the drug was removed from the market. In 2009, when it was found that horses de-wormed with the anthelmintic levamisole, metabolized that drug to aminorex, the same drug that caused the 1970s outbreak of PAH. The discovery would not have been cause for concern except to horseracing enthusiasts, who feared horse doping. However, at about the same time the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…In healthy individuals who ingested high doses of pure levamisole, comparatively small amounts of aminorex were found in plasma and urine118,119. It seems to be the case that the conversion rate from levamisole to aminorex might be quite low121,122. Still, Karch et al .…”
Section: Historical Contextmentioning
confidence: 99%
See 2 more Smart Citations
“…In healthy individuals who ingested high doses of pure levamisole, comparatively small amounts of aminorex were found in plasma and urine118,119. It seems to be the case that the conversion rate from levamisole to aminorex might be quite low121,122. Still, Karch et al .…”
Section: Historical Contextmentioning
confidence: 99%
“…Eiden et al found levamisole in 75% of all analyzed urine samples yet aminorex could not be detected . In healthy individuals who ingested high doses of pure levamisole, comparatively small amounts of aminorex were found in plasma and urine. , It seems to be the case that the conversion rate from levamisole to aminorex might be quite low. , Still, Karch et al describe the case of a deceased long-term poly drug user with systemically detectable levamisole and aminorex levels who might have suffered from idiopathic pulmonary arterial hypertension, and it has been shown that levamisole accumulates in lung tissue. Deaths due to levamisole or aminorex toxicity associated with the consumption of cocaine have rarely been reported. , At this point, it is known that only a small fraction of levamisole is metabolized into aminorex and its (side) effects seem negligible when compared to those observed with levamisole. Future studies should explore the prevalence of pulmonary arterial hypertension in long-term, high-dose users of levamisole-adulterated cocaine.…”
Section: Historical Contextmentioning
confidence: 99%
See 1 more Smart Citation
“…15 Soon afterwards, aminorex was found in human urine after controlled oral intake of levamisole. 17 From then on, it is often cited as a human metabolite of PTHIT [18][19][20] even though data relating to the analytical proof of aminorex in forensic samples is still quite rare and contradictory in the literature. 10,21 Moreover, there are further less known putative metabolites of PTHIT sharing the same sum formula (C 9 H 10 N 2 O).…”
Section: Introductionmentioning
confidence: 99%